High Electrochemical Performance of Bi2WO6/Carbon Nano-Onion Composites as Electrode Materials for Pseudocapacitors - Zhang, Weike; Peng, Lin; Wang, Jiawei; Guo, Chunli; Chan, Siew Hwa; Zhang, Lan (Frontiers in Chemistry, 2020)
Bi2WO6/CNOs (CNOs, carbon nano-onions) composites are synthesized via facile low-cost hydrothermal method and used as electrode of pseudocapacitors. X-ray diffraction (XRD), fourier transform infrared spectra (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), N2 adsorption-desorption techniques and X-ray photoelectron spectroscopy (XPS) measurements are used to characterize the synthesized composite powders. Electrochemical performances of the composites electrode are studied by cycle voltammetry, charge-discharge and electrochemical impedance spectroscopy methods. Results indicate that the specific capacitance of the Bi2WO6/CNOs composite materials reach up to 640.2 F/g at a current density of 3 mA/cm2 and higher than that of pristine Bi2WO6, 359.1 F/g. The capability of prepared pseudocapacitor remain 90.15% after 1000 cycles charge-discharge cycling measurement. The cell performance and stability can be enhanced by further optimization and modification of the composition and microstructure of the electrode of the cell.